E-Political Campaign in the 2014 Presidential Election in Indonesia - Yuliatiningtyas, Solikhah (Jurnal Ilmu Sosial dan Humaniora, 2022)
Until 2014, only members of the political and military elite have been elected as presidents in Indonesia. The new president, Joko Widodo (known as Jokowi) is the first leader from outside the establishment of political habits to be elected directly by citizens. It uses ‘Tri-angulation Methods’: in-depth interviews with prominent politicians/advisors from six parties, focus group discussion and Critical Discourse Analysis/CDA of e-campaigns. This paper to explain why Jokowi won the election, and what campaign strategies used. The findings show television still has the highest percentage of usage for campaigns, followed by social media. Two parties (Gerindra and PKB) which focused on e-campaigns, have successfully increased their electability, especially by gaining votes among young voters. Although Prabowo’s votes increased 35% but it couldn’t beat Jokowi’s votes. There were four factors that caused Jokowi to win the presidential election despite a poor e-campaign from his party. Firstly, the shaping of his image by traditional media which influenced grass-roots society, people who don’t usually have access to the internet. This social fact has resulted in Jokowi becoming the most popular politician in Indonesia and being finally crowned as a presidential candidate by Megawati, the Chairman of PDI-P Party. Unlike Europe and US, traditional media had set out the public agenda to influence the election, in contrast with agenda aetting theory (AST) practice that is used widely. Secondly, the role of an Islamic Party (PKB) which nominated a vice president (JK) with Jokowi. PKB used integrated campaign strategies: traditional (involving 3000 Islamic scholars) and e-campaign methods managed by PKB’s 500 young cadres and 2 million volunteers. Thirdly, a strong role model of Muslim women in Nahdlatul Ulama (NU), the biggest Islamic organization in Indonesia. The PKB party, as part of NU, together with the Muslim women organization, succeeded in neutralizing black campaigns which attacked Jokowi’s religious integrity. Finally, unofficial e-media campaigns organized by PKB and civil society volunteers as well as feeding publications among traditional mass media were also considered to be a strong factor. Through this well managed combination of traditional and new media campaigns, Jokowi won 53.15 percent of the votes, 6.3 percent more than Prabowo’s 46.85 percent. It concludes with assessments of the importance of e-media to the presidential election campaigns of Jokowi and Prabowo, and of the value of social media in increasing political participation, especially by young people.